Genetic algorithm applied in the analysis of economic viability of the implantation of biodigesters in dairy cattle - Moura Novo, João Pedro; Marcos Cossi, Antonio; Regina Nugoli Estevam, Celia (Seven Editora, 2023)
In Brazil, energy consumption is increasing on a large scale, while the number of energy demand grows slowly by small percentages each year. Rural properties intended for raising pigs and cattle for milking have enormous energy potential, since they are the most suitable for the implementation of the biodigester, due to the amount of waste that these animals produce and the ease of collecting them, as long as they are reared in confinement most of the time. Thus, this work presents a linear optimization model to evaluate the feasibility of implementing biodigesters as a source of electrical energy in rural properties intended for dairy cattle. To evaluate the results of the proposed model, simulations of cases applied in three cattle ranching properties are presented, located in the northwest of the state of Sao Paulo, are presented. For the simulations, we used a website (Web application) developed specifically to address the economic feasibility of implementing biodigesters. DOI: https://doi.org/10.56238/tfisdwv1-054